Triterpene and Steroid Glycosides from Marine Sponges (Porifera, Demospongiae): Structures, Taxonomical Distribution, Biological Activities - Natalia V. Ivanchina; Vladimir I. Kalinin (Molecules, 2023)
The article is a comprehensive review concerning tetracyclic triterpene and steroid glycosides from sponges (Porifera, Demospongiae). The extensive oxidative transformations of the aglycone and the use of various monosaccharide residues, with up to six possible, are responsible for the significant structural diversity observed in sponge saponins. The saponins are specific for different genera and species but their taxonomic distribution seems to be mosaic in different orders of Demospongiae. Many of the glycosides are membranolytics and possess cytotoxic activity that may be a cause of their anti-predatory activities. All these data reveal the independent origin and parallel evolution of the glycosides in different taxa of the sponges. The information concerning chemical structures, biological activities, biological role, and taxonomic distribution of the sponge glycosides is discussed.